2020
DOI: 10.1371/journal.pone.0229029
|View full text |Cite
|
Sign up to set email alerts
|

Gut dysbiosis is prevailing in Sjögren’s syndrome and is related to dry eye severity

Abstract: Objective To investigate gut dysbiosis in patients with Sjö gren's syndrome (SS) or dry eye syndrome (DES) compared to normal subjects and to evaluate the association of dysbiosis with dry eye severity. Methods 10 subjects with SS, 14 subjects with DES and 12 controls were enrolled. Corneal staining, tear break up time (TBUT) and tear secretion were evaluated. Bacterial genomic 16s rRNA from stool samples were analyzed. Main outcomes were microbiome compositional differences among groups and their correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
144
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(156 citation statements)
references
References 47 publications
11
144
1
Order By: Relevance
“…Sjögren's syndrome (SS) is an autoimmune condition characterized by lymphocytic infiltration in exocrine glands, particularly the lacrimal glands, causing dry eyes [82,83]. Moon et al recently published a study in which changes in the gut microbiota were found to be associated with SS in human subjects compared to healthy volunteers and subjects with environmental dry eye syndrome (DES) [82].…”
Section: Sjögren's Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Sjögren's syndrome (SS) is an autoimmune condition characterized by lymphocytic infiltration in exocrine glands, particularly the lacrimal glands, causing dry eyes [82,83]. Moon et al recently published a study in which changes in the gut microbiota were found to be associated with SS in human subjects compared to healthy volunteers and subjects with environmental dry eye syndrome (DES) [82].…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…Sjögren's syndrome (SS) is an autoimmune condition characterized by lymphocytic infiltration in exocrine glands, particularly the lacrimal glands, causing dry eyes [82,83]. Moon et al recently published a study in which changes in the gut microbiota were found to be associated with SS in human subjects compared to healthy volunteers and subjects with environmental dry eye syndrome (DES) [82]. SS was associated with a decreased F/B ratio, decreased Actinobacteria, and decreased abundance of members of the Bifidobacterium, Blautia, Dorea, and Agathobacter genera, with increased abundance of members of the Prevotella, Odoribacter, and Alistipes genera [82].…”
Section: Sjögren's Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the current study is the lack of information on the gut microbiota. Gut microbial dysbiosis has also been reported in SS patients particularly in association with dry eyes 12 , 36 . There is a possibility that the gut microbiota contributed to the development and mitigation of FLS in the noncohoused and cohoused Nfkbiz −/− mice, respectively, through regulation of the common mucosal immune system.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies analyzed the gut microbiome in pSS patients [6][7][8][9][10], but for some reason Mendez et al limited the comparison of their data only to the study by de Paiva et al [7]. Mendez et al stated that a similar decrease in relative abundance of Faecalibacterium and Bacteroides was found in both studies [1,7].…”
Section: Dear Editormentioning
confidence: 99%